PHYTOTOXICOLOGICAL STUDY OF SOME SPIROHYDANTOINS AND THEIR DERIVATIVES TOWARDS PSEUDOCROSSIDIUM REVOLUTUM - Ganchev, Donyo; Marinov, Marin; Krustev, Stefan; Zlateva, Milena; Atanasova, Nadezhda; Stoyanov, Neyko (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
This article presents a novel ecotoxicological investigation of probable deleterious effect of cyclopentanespiro-5-hydantoin, cyclohexanespiro-5-hydantoin, cyclopentanespiro-5-(2,4-dithiohydantoin) and 1-aminocyclopentanecarboxylic acid towards some of the most widespread moss species in the World – Pseudocrossidium revolutum.. Dose-response modeling was carried out by R language for Statistical Computing, drc package.